2012
DOI: 10.1128/aem.07829-11
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Cryptosporidium parvum Oocysts in Soil Columns following Applications of Raw and Separated Liquid Slurries

Abstract: ABSTRACTThe potential for the transport of viableCryptosporidium parvumoocysts through soil to land drains and groundwater was studied using simulated rainfall and intact soil columns which were applied raw slurry or separated liquid slurry. Following irrigation and weekly samplings over a 4-week period,C. parvumoocysts were detected from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
4
19
1
Order By: Relevance
“…Others have reported that E. coli O157:H7 and S. enterica Typhimurium applied as dairy cattle manure or fecal slurry both decreased 2 to 4 log CFU • (g dry weight of soil) -1 over 40 cm of sandy soil with 24 hours of simulated rainfall (Semenov et al, 2009). Our results and others are in contrast to those for Cryptosporidium parvum oocysts, where there oosyst abundance in loamy-sand soil declined only one log over 20 cm (Petersen et al, 2012). Similarly, Boyer et al (2009) reported a decline in C. parvum from 1.5 to 0.1 oocysts • (g soil) -1 over 50 cm of silt loam soil (Boyer et al, 2009).…”
Section: Discussioncontrasting
confidence: 77%
“…Others have reported that E. coli O157:H7 and S. enterica Typhimurium applied as dairy cattle manure or fecal slurry both decreased 2 to 4 log CFU • (g dry weight of soil) -1 over 40 cm of sandy soil with 24 hours of simulated rainfall (Semenov et al, 2009). Our results and others are in contrast to those for Cryptosporidium parvum oocysts, where there oosyst abundance in loamy-sand soil declined only one log over 20 cm (Petersen et al, 2012). Similarly, Boyer et al (2009) reported a decline in C. parvum from 1.5 to 0.1 oocysts • (g soil) -1 over 50 cm of silt loam soil (Boyer et al, 2009).…”
Section: Discussioncontrasting
confidence: 77%
“…Moreover, Cryptosporidium contamination of water sources through surface run-off from faeces deposited on agricultural land has repeatedly been documented (Tate et al, 2000;Davies et al, 2004;Thurston-Enriquez et al, 2005). In addition, Petersen et al (2012) demonstrated that C. parvum oocysts present in pig slurry applied to soil can leach and potentially contaminate groundwater. Cryptosporidiosis and giardiasis are widespread and debilitating diseases in calves, and cattle often host the zoonotic C. parvum and to a lesser degree also G. duodenalis Assemblage A.…”
mentioning
confidence: 99%
“…The inlet pipe of the septic tank had crossed above the water pipe to the underground water tank. There was soil between the pipes of the septic tank and the underground water storage tank; however, oocysts and bacteria muct have passed the soil as reported by some authors [7,27]. The cleaning work of the underground water tank just before the outbreak seems to have made the situation worse.…”
Section: Discussionmentioning
confidence: 91%